Software Engineering Practices in Early Stages of Icelandic Software Startups - Artifacts and work documents ... - Helgason, Elvar (https://b2share.eudat.eu, 2020)
Supplementary material for thesis: Software Engineering Practices in Early Stages of Icelandic Software Startups, M.Sc. thesis in Software Engineering, Faculty of Industrial Engineering, Mechanical Engineering and Computer Science, University of Iceland. Artifacts generated while performing interviews and grounded theory analysis. Interview guide (PDF documents): Version 1.2 received from Helgi Þorbergsson, University of Iceland and Rory V. O'Connor, Dublin City University designed for prior unfinished research. Changed as necessary while interviewing process took place to limit extraneous questions and improve discussion flow. Coded transcripts (Microsoft Word documents): A transcript for each interview used in research. Also includes open codes as comments, with memos as necessary, linked to select text from the transcripts. The transcripts have been anonymized. Open, axial, and selective codes Microsoft Excel documents: open_codes.xlsx contains open code information extracted from coded transcript ...